Blue Light Improves Stomatal Function and Dark-Induced Closure of Rose Leaves (Rosa x hybrida) Developed at High Air Humidity - Terfa, Meseret Tesema; Olsen, Jorunn Elisabeth; Torre, Sissel (Frontiers in Plant Science, 2020)
Plants developed under constant high (>85%) relative air humidity (RH) have larger stomata that are unable to close completely in response to closing stimuli. Roses (Rosa x hybrida) developed in high RH have previously been shown to have high water loss during leaf dehydration and reduced dark-induced closure resulting in a shorter postharvest life. In this study, the effect of B-light on stomatal function under high RH conditions was investigated. The ability of rose leaves developed under continuous high (90%) or moderate (60%) RH to close their stomata in response to darkness and leaf dehydration assay was studied. Moreover, the level and regulation of ABA in light and darkness in relation to B-light was measured. Our results show that increased B-light proportion improved stomatal function and dark-induced stomatal closure under high RH conditions and that was associated with increased [ABA] in general and a dynamic ABA peak during darkness. Furthermore, increased B-light during the day was associated with the presence of high β-glucosidase activity during night. This indicates that B-light is important as a signal to activate the β-glucosidase enzyme and release ABA during night. Altogether, the improved stomatal function and reduced transpiration in combination with increased [ABA] indicate that preharvest B-light plays an important role in governing stomatal functionality and ABA homeostasis under high RH and can be a useful method to improve postharvest water balance of roses.